P160 A trial of a position modification device for the prevention of supine sleep during pregnancy. (7th October 2021) - Wilson, D; Whenn, C; Walker, S; Barnes, M; Howard, M
Abstract: Self-reported supine position at sleep onset during late pregnancy is related to a 2.6x increase in stillbirth risk, possibly due to the enlarged uterus compressing major blood vessels supplying the placenta. This study aimed to test the effectiveness of a pillow designed to decrease supine sleep in pregnant women. Twelve women in the third trimester of pregnancy used their own pillows for a control week and the intervention pillow for 1 week, in randomised order. Sleep position for each night of both weeks was monitored with the Night Shift Sleep Positioner, with a sleep study (WatchPat300) on the last night of each week to measure the impact of the intervention on SDB. During the control week, the women slept supine for a median of 19.9% (IQR = 11.6, 27.4) of total sleep time (TST), compared to a median of 20.4% (10.2, 31.0) TST using the intervention pillow (p = .64). Use of the intervention pillow did not impact sleep efficiency (control = 85.3% (80.7, 88.0) v. intervention = 85.2% (78.3, 89.0), p = .48). On the sleep study night, supine sleep was reduced in the intervention compared to control condition (12.9% vs. 17.7%, p = .04), but AHI did not differ (intervention = 2.6/hr (0.8, 6.7) vs. control = 1.5/hr (0.6, 3.6), p = .11). We found that the adoption of a pillow designed to discourage supine sleep was not effective in late pregnancy. Considering the reasonably high amount of supine sleep in our participants, alternative devices should be investigated.